2020
DOI: 10.1111/jmi.12877
|View full text |Cite
|
Sign up to set email alerts
|

HAADF‐STEM image analysis for size‐selected platinum nanoclusters

Abstract: SummaryIn this study, size‐selected platinum (Pt) nanoclusters were imaged with aberration‐corrected scanning transmission electron microscopy in high‐angle annular dark field (HAADF) mode. For image analysis, a relatively simple macro program was developed by making the use of existing ImageJ plug‐ins. The macro allows effectively for assessing criterions chosen for intensity threshold and filter blurring factors. It can extract the integrated HAADF intensity, peak intensity and projected area of the clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…For these reasons, integrated HAADF intensity is a more robust descriptor for small metal clusters. 46 High-resolution imaging of the Pt 147 clusters on WS 2 as shown in Figure S10 reveals predominantly noncrystalline structures, with structural features indicative of partial icosahedral motifs, which is consistent with the findings of Lambie et al 27 Larger sintered clusters, identified through their integrated HAADF intensity, are observed to have crystalline FCC structures.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…For these reasons, integrated HAADF intensity is a more robust descriptor for small metal clusters. 46 High-resolution imaging of the Pt 147 clusters on WS 2 as shown in Figure S10 reveals predominantly noncrystalline structures, with structural features indicative of partial icosahedral motifs, which is consistent with the findings of Lambie et al 27 Larger sintered clusters, identified through their integrated HAADF intensity, are observed to have crystalline FCC structures.…”
Section: Resultssupporting
confidence: 86%
“…The projected area distribution of the Pt 147 clusters is broader (i.e., width divided by mean value) than the integrated intensity distribution due to various reasons, including thresholding uncertainties and differing Pt 147 arrangements and structures on the WS 2 surface. For these reasons, integrated HAADF intensity is a more robust descriptor for small metal clusters . High-resolution imaging of the Pt 147 clusters on WS 2 as shown in Figure S10 reveals predominantly noncrystalline structures, with structural features indicative of partial icosahedral motifs, which is consistent with the findings of Lambie et al Larger sintered clusters, identified through their integrated HAADF intensity, are observed to have crystalline FCC structures.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…It is noted that because not all of the Pt nanoparticles are fully in focus in the images, these presented particle sizes (based on the projected area in the images) are an upper estimate of the particle size. The actual sizes of the measured particles in the electron beam are likely somewhat smaller (Xia et al 29 ). XRD.…”
Section: ■ Errors In Analysismentioning
confidence: 99%